El efecto de la jornada complementaria escolar en Cundinamarca sobre variables de desempeño académico de los participantes (2017)
"The Complementary School Day (Jornada única) in Cundinamarca was a program designed to reinforce the academic performance of students and promote the development of artistic and cultural capacities. The evaluation of this type of program is of great importance, since the Government allocates much of the budget to improve the school coverage. In this way it is important to estimate the impact of the program on the beneficiaries in academic terms specifically on school dropout and repetition. This project assesses the effects of this program estimating a logit model. We found positive effects on participants' dropouts, however, repetition increases. This could happen, because the program maintains in the system students of the left tail of the distribution in abilities and these same ones will increase the repetition. There are also heterogeneous effects between 1) men and women, 2) primary and secondary, and 3) years in which the program was implemented".-- Tomado del Formato de Documento de Grado.